IMPROVING THE MANAGEMENT SYSTEM OF EDUCATIONAL QUALITY CONTROL MECHANISMS (International journal of artificial intelligence, 2025)
This article explores the methodological and strategic foundations for improving the management system of educational quality control mechanisms, drawing upon the best practices and policy frameworks adopted in developed countries. It critically analyzes the strengths and limitations of existing control systems in the context of digital transformation, with a focus on enhancing transparency, accountability, and data-driven governance. The study emphasizes the integration of advanced digital technologies—such as artificial intelligence, learning analytics, and cloud-based platforms—into national education management structures to support real-time quality monitoring and decision-making. Case studies from countries such as Finland, Singapore, and South Korea are examined to identify transferable models of educational supervision and performance evaluation. Furthermore, the paper proposes a conceptual framework for Uzbekistan, combining international standards with localized policy mechanisms to ensure sustainable and scalable improvement in educational quality. The findings of this research aim to contribute to the modernization of national education quality assurance systems, strengthen institutional capacity, and align governance processes with global benchmarks for educational excellence.